Developing definitions of research information metadata as a wicked problem? Characterisation and solution by argumentation visualisation. Issue 3 (4th July 2016) - Riechert, Mathias; Biesenbender, Sophie; Dees, Werner; Sirtes, Daniel
Abstract : Purpose: – The purpose of this paper is to focus on the development of definitional standards for research information as a wicked problem. A central solution strategy for such problems, increasing transparency by argumentation visualisation, is being evaluated. Design/methodology/approach: – Qualitative formal content analysis is used in order to examine whether the process of definition standardisation in the project can be characterised as a wicked problem. Action Research is used to assess the effect of argumentation visualisation in the project. Findings: – The results of the content analysis confirm the interpretation of the standardisation process as a wicked problem. The implementation of argumentation visualisation shows to increase the meetings' focus and effectiveness. Research limitations/implications: – The relationship between information exchange, transparency and acceptance of the development result should be addressed in future empirical analyses. Visualisation solutions require further development in order to accommodate needs of the stakeholders. Practical implications: – Argumentation visualisation is of high value for finding a consensus for definitional standards and should be considered for managing and exchanging information. Originality/value: – Applying solution strategies from design research on wicked problems to large-scale standardisation efforts opens up new possibilities for not only handling such projects but also providing new avenues of research for both the design and research information communities.